C-type natriuretic peptide concentrations in the plasma and cerebrospinal fluid of patients with subarachnoid hemorrhage - Ikeda, Kazumi (BioMed Central, 2001)
BACKGROUND: Cerebral vasospasm is a poor resulting outcome of a ruptured cerebral aneurysm; to clarify the mechanism of vasospasm it is important to improve this outcome. C-type natriuretic peptide (CNP) is present in the brain as a cerebral vasodilator; it is also an endothelium-derived relaxing factor produced via cGMP. We speculated that CNP might be an inhibitor of cerebral vasospasm after subarachnoid hemorrhage (SAH). METHODS: To clarify the role of CNP in cerebral vasospasm after SAH, we conducted 1 week monitoring of CNP concentrations in the plasma and cerebrospinal fluid (CSF) of 26 patients who had undergone clipping within 24 hours of the occurrence of SAH, and divided them into group A (positive for angiographic spasm) and group B (negative for angiographic spasm). We also examined CNP concentrations in the CSF of patients who were receiving spinal anesthesia for small orthopedic operations, as reference patients. RESULTS: The CNP concentration in the CSF on day 1 was higher than in the reference patients and decreased in both test groups, but we did not observe any significant difference between the groups. CNP concentrations in the plasma did not change in either group. CONCLUSIONS: CNP concentrations in the CSF were high in the acute phase after SAH, whereas plasma CNP concentrations remained constant. However, our findings did not support our hypothesis because we did not find any relationship between vasospasm and changes in CNP concentrations in the CSF.